ENPP2 inhibitor improves proliferation in AOM/DSS-induced colorectal cancer mice via remodeling the gut barrier function and gut microbiota composition - Junling Yan; Wenting Duan; Qinhan Gao; Tianxiao Mao; Majie Wang; Jialin Duan; Jiankang Li (Elsevier, 2023)
In our previous multicenter study, we delineated the inherent metabolic features of colorectal cancer (CRC). Therein, we identified a member of the ectonucleotide pyrophosphatase/ phosphodiesterase family (ENPP2) as a significant differential metabolite of CRC. In this study, the role of ENPP2 in CRC has been demonstrated using established in vitro and in vivo models including ENPP2 gene knockdown, and use of the ENPP2 inhibitor, GLPG1690. We found that CRC proliferation was decreased after either ENPP2 gene knockdown or use of ENPP2 inhibitors. We further evaluated the role of GLPG1690 in AOM/DSS-induced CRC mice via intestinal barrier function, macrophage polarization, inflammatory response and microbial homeostasis. Results of immunofluorescence staining and Western blotting showed that GLPG1690 can restore gut-barrier function by increasing the expression of tight junction proteins, claudin-1, occludin and ZO-1. M2 tumor-associated macrophage polarization and colonic inflammation were attenuated after treatment with GLPG1690 using the Azoxymethane/Dextran Sodium Sulfate (AOM/DSS) model. Moreover, 16 S rDNA pyrosequencing and metagenomic analysis showed that GLPG1690 could alleviate gut dysbiosis in mice. Furthermore, administration of GLPG1690 with antibiotics as well as fecal microbiota transplantation assays demonstrated a close link between the efficacy of GLPG1690 and the gut microbiota composition. Finally, results of metabolomic analysis implicated mainly the gut microbiota-derived metabolites of aromatic amino acids in CRC progression. These findings may provide novel insights into the development of small-molecule ENPP2 inhibitors for the treatment of CRC.